Hubungan Berkendara Sepeda Motor Terhadap Risiko Terjadinya Nyeri Punggung Bawah - Abdurahman Berbudi B L; Nina Mustika Sari; Liza Laela Abida (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Low back pain is a disorder that occurs in the lower back area due to pinched nerves, muscle tension, herniated nucleus pulposus, disorders of the spine and joints, low back pain can cause discomfort and interfere with one's productivity, there are many factors that affect low back pain such as age, ergonomics when lifting goods, work position, Body Mass Index, riding a motorcycle. This research is a descriptive study with a cross-sectional study design. The research subjects included members of the Bekasi City Association and the people of Pamulang. Data analysis was performed using the chi-square test and ordinal regression. The results showed that the risk factors for low back pain had a significant relationship such as age, body mass index, ergonomics, exercise habits, work, and motorcycle driving value p <0.05. Body mass index, which is obtained due to low exercise activity, ergonomic factors when working lifting goods and when driving can trigger the sensation of lower back pain, while risk factors such as smoking habits, gender, years of service have no significant relationship where the value of p> 0.05 , because smoking and years of work are not a very determining factor, as well as gender in this study more men, whereas based on previous research women are more at risk of developing low back pain.